On the problem of error propagation in classier chains for multi-label classification. Data Analysis, Machine Learning and Knowledge Discovery - Senge, Robin; del Coz, J.J.; Hüllermeier, Eyke (In Proceedings of GFKL-2012, 36th Annual Conference of the German Classification Society, Studies in Classification, Data Analysis and Knowledge Organization, Hildesheim, Germany)

Local clique merging: An extension of the maximum common subgraph measure with applications in structural bioinformatics, Algorithms from and for Nature and Life - Fober, T.; Klebe, G.; Hüllermeier, Eyke (In Proceedings GFKL-2011, Conference of the German Classification Society, Frankfurt Germany)

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013,)

DAG - Index - A Compressed Index for XML Keyword Search - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (WEBIST 2013 - Proceedings of the 9th International Conference on Web Information Systems and Technologies)

Ordinal Choquistic regression - Fallah Tehrani, A.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2013 8th International Conference on the European Society for Fuzzy Logic and Technology, Milano, Italy)

Fuzzy Pattern Trees as an alternative to rule-based fuzzy systems: Knowledge-driven, data-driven and hybrid modeling of colour yield in poyester dyeing, Edmonton, Canada - Nasiri, N.; Fober, T.; Senge, Robin; Hüllermeier, Eyke (in Proceedings IFSA-2013 World Congress of the International Fuzzy Systems Association, Edmonton, Canada)

Implementing Efficient Updates in Compressed Big Text Databases - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita; Schlüßler, Jonathan (International Conference on Database and Expert Systems Applications)

How visualization courses have changed over the past 10 years - Owen, G Scott; Domik, Gitta; Ebert, David S; Kohlhammer, J{\; Rushmeier, Holly; Santos, Beatriz Sousa; Weiskopf, Daniel (IEEE computer graphics and applications)

Animatronics Workshop: A Theater+ Engineering Collaboration at a High School - Alford, Jennifer Ginger; Jacob, Lucas; Dietz, Paul (IEEE computer graphics and applications)

Visualizing Dissections of the Heart in a Dataflow-based Shader Framework for Volume Rendering - Arens, Stephan; Bolte, Matthias; Domik, Gitta (Vision, Modeling & Visualization)

Multilabel classification for exploiting cross-resistance information in HIV-1 drug resistence prediction - Heider, D.; Senge, Robin; Cheng, W.; Hüllermeier, Eyke (Bioinformatics)

Chest pain in primary care: is the localization of pain diagnostically helpful in the critical evaluation of patients? A cross sectional study. - Bösner, S.; Bönisch, K.; Haasenritter , J.; Schlegel, P.; Hüllermeier, Eyke; Donner-Banzhoff, N. (BMC Family Practice)

Diagnose im Kontext - eine erweiterte Perspektive - Haasenritter, J.; Viniol, A.; Becker, A.; Bösner, S.; Hüllermeier, Eyke; Senge, Robin; Donner-Banzhoff, N. (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen (ZEFQ))

Evolving fuzzy pattern trees for binary classification on data streams - Shaker, A.; Senge, R.; Hüllermeier, Eyke (Information Sciences)

Spherical Visibility Sampling - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Computer Graphics Forum)
Many 3D scenes (e.g. generated from CAD data) are composed of a multitude of objects that are nested in each other. A showroom, for instance, may contain multiple cars and every car has a gearbox with many gearwheels located inside. Because the objects occlude each other, only few are visible from outside. We present a new technique, Spherical Visibility Sampling (SVS), for real-time 3D rendering of such -- possibly highly complex -- scenes. SVS exploits the occlusion and annotates hierarchically structured objects with directional visibility information in a preprocessing step. For different directions, the directional visibility encodes which objects of a scene's region are visible from the outside of the regions' enclosing bounding sphere. Since there is no need to store a separate view space subdivision as in most techniques based on preprocessed visibility, a small memory footprint is achieved. Using the directional visibility information for an interactive walkthrough, the potentially visible objects can be retrieved very efficiently without the need for further visibility tests. Our evaluation shows that using SVS allows to preprocess complex 3D scenes fast and to visualize them in real time (e.g. a Power Plant model and five animated Boeing 777 models with billions of triangles). Because SVS does not require hardware support for occlusion culling during rendering, it is even applicable for rendering large scenes on mobile devices.

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

A3.2 - Design, modeling and identification of an ultrasonic composite transducer for target impedance independent short pulse generation - Bause, F.; Rautenberg, J.; Henning, Bernd

3.2 - Infrared reflectance measurements of thin films with time variable surface roughness or texture - Hoof, C.; Wetzlar, D.; Henning, Bernd

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)